Electronic cigarette use enriches periodontal pathogens. (22nd January 2022) - Xu, Fangxi; Pushalkar, Smruti; Lin, Ziyan; Thomas, Scott C.; Persaud, Julia Kishanie; Sierra, Maria A; Vardhan, Mridula; Vasconcelos, Rebeca; Akapo, Adenike; Guo, Yuqi; Gordon, Terry; Corby, Patricia M; et al.
Abstract: The effect of electronic cigarette (e‐cigarette) smoking, especially its long‐term impact on oral health, is poorly understood. Here, we conducted a longitudinal clinical study with two study visits, 6 months apart, to investigate the effect of e‐cigarette use on the bacterial community structure in the saliva of 101 periodontitis patients. Our data demonstrated that e‐cigarette use altered the oral microbiome in periodontitis patients, enriching members of the Filifactor, Treponema, and Fusobacterium taxa. For patients at the same periodontal disease stage, cigarette smokers and e‐cigarette smokers shared more similarities in their oral bacterial composition. E‐cigarette smoking may have a similar potential as cigarette smoking at altering the bacterial composition of saliva over time, leading to an increase in the relative abundance of periodontal disease‐associated pathogens such as Porphyromonas gingivalis and Fusobacterium nucleatum . The correlation analysis showed that certain genera, such as Dialister, Selenomonas, and Leptotrichia in the e‐cigarette smoking group, were positively correlated with the levels of proinflammatory cytokines, including IFN‐γ, IL‐1β, and TNF‐α. E‐cigarette use was also associated with elevated levels of proinflammatory cytokines such as IFN‐γ and TNF‐α, which contribute to oral microbiome dysbiosis and advanced disease state.